Intravitreal Injections of Voriconazole for Candida Endophthalmitis: A Case Series. (2nd April 2020) - Bienvenu, Anne-Lise; Aussedat, Marine; Mathis, Thibaud; Guillaud, Martin; Leboucher, Gilles; Kodjikian, Laurent
ABSTRACT: Purpose : Candida endophthalmitis represents a therapeutic challenge, considering the inability of many antifungals to achieve adequate concentrations in the vitreous. Intravitreal injection (IVI) of antifungals (amphotericin b deoxycholate or voriconazole) is therefore recommended. Whereas amphotericin b IVI is well documented, clinical data on voriconazole IVI are limited. Methods : This was a retrospective review IRB approved of patients receiving voriconazole IVI for Candida endophthalmitis. Complete ophthalmological examination was completed at baseline and during follow-up. Results : Five patients were treated with a mean four injections [range: 2–9] of voriconazole (100 µg/0.1 mL saline). Improvement of visual acuity and disappearance of signs of infection were obtained in all patients. Safety concern including photoreceptor toxicity was not attributed to voriconazole IVI. Conclusions : Voriconazole IVI demonstrated to be safe and led to a favorable clinical outcome. Thus, voriconazole IVI must be performed if Candida endophthalmitis is suspected to increase the chance of clinical success.